2018
DOI: 10.4172/2161-1017.1000283
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Maximum and Optimum Doses of Hydroxychloroquine Added to Patients with Poorly Controlled Type 2 Diabetes on Stable Insulin Therapy along with Glimepiride And Metformin: Association of High-Sensitive C-Reactive Protein (Hs-CRP) and Glycosylated Haemoglobin (Hba1c)

Abstract: Aim: To determine the efficacy of maximum and optimum dosages of hydroxychloroquine (400 and 200 mg once daily) treatment combined with insulin along with metformin and Glimepiride in Type 2 diabetes patients who are poorly controlled and relationship to be evaluate between high-sensitive C-reactive protein (Hs-CRP) and glycosylated haemoglobin (HbA1c) levels in such patients. Methods: In a multicentre,open-labelled comparative observational study, randomised 240 patients [mean age 56.44 years and mean body ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In recent clinical study, it has been shown that HCQ has reduced total daily insulin dose by 28% with 1.3% HbA1c reduction from baseline in patients with poorly controlled type 2 diabetes on stable insulin therapy along with glimepiride and metformin. 7 In this study we had noticed a significant HbA1c reduction with addition of HCQ 400mg in patients uncontrolled on glimepiride 2mg and metformin 1000mg. This reduction of HbA1c was higher than the up titration of either metformin or glimepiride dose.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In recent clinical study, it has been shown that HCQ has reduced total daily insulin dose by 28% with 1.3% HbA1c reduction from baseline in patients with poorly controlled type 2 diabetes on stable insulin therapy along with glimepiride and metformin. 7 In this study we had noticed a significant HbA1c reduction with addition of HCQ 400mg in patients uncontrolled on glimepiride 2mg and metformin 1000mg. This reduction of HbA1c was higher than the up titration of either metformin or glimepiride dose.…”
mentioning
confidence: 69%
“…In recent clinical study, it has been observed that HCQ has reduced total daily insulin dose by 28% with 1.3% HbA1c reduction from baseline. 7 In another trial, uncontrolled type 2 diabetes patients (HbA1c: 7.5-11.5%) on a combination of metformin 1000mg/day and glimepiride 4mg/day or gliclazide 160mg/day were randomized to receive either hydroxychloroquine 400mg/day (n=135) or pioglitazone 15mg/day (n=132) for 24 weeks. There was a significant reduction in the mean HbA1c, FBG and PPG from baseline at week 24 in both the groups.…”
mentioning
confidence: 99%
“…Besides, this drug can suppress inflammatory biomarkers and control the lipid profile levels, resulting in a reduced risk of DM [17,18]. Furthermore, reduction in hemoglobin A1c (HbA1c) fasting plasma glucose (FPG) and postprandial blood glucose (PPBG) levels are established in various studies [17,[19][20][21][22]. Therefore, this review is aimed at assessing the efficacy of HCQ therapy in experimental models of DM and diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a prospective, randomized, placebo, double-blind 6-month trial the addition of Hydroxychloroquine to either insulin or glibenclamide in the treatment of refractory noninsulin-dependent diabetes for 6 months resulted in a signi icant decrease in HbA1C by 3.3% compared with placebo as well as a reduction in insulin dose by 30% in the insulin-treated group [11]. In a recent RTCT trial conducted by Baidya et al [12], con irms that in type 2 diabetes patients who are poorly controlled, addition of hydroxychloroquine (HCQ) to insulin along with Glimepiride and Metformin, there was signi icant overall mean change in total daily insulin dose at study end by almost 28% with a HbA1c reduction of -1.3% from baseline within 6 months. When Hydroxychloroquine was evaluated against Teneligliptin in patient who were uncontrolled on Metformin 2000 mg and Glimepiride 2 mg, a further HbA1c reduction of -1.8% happened with Hydroxychloroquine than compared to Teneligliptin with which it was -1.3% [13].…”
Section: Introductionmentioning
confidence: 99%